Republic of Lithuania : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, Insurance Regulation, and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2002)
This paper presents key findings of the Financial System Stability Assessment for the Republic of Lithuania, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, Insurance Regulation, and Payment Systems. There appear to be no immediate threats to the stability of the bank-dominated financial system, owing to sound macroeconomic policies in the context of the currency board arrangement, vigorous structural and legal reforms in preparation for accession to the European Union, and strong banking regulation and supervision.